Why Do Albania Doctors Migrate? (European Journal of Interdisciplinary Studies, 2017)
Migration has become a very topical political and economic concern over the past few years, with particular reference to human migration from developing countries to more developed countries. Health workforce migration from the countries in Western Balkans, especially from Albania to more developed countries is increasing during the past few years according to official statement of medical associations. So, last three years 400 doctors have asked for certificate of “Good standing” in order to apply for a job abroad. Thus, the migration of healthcare personnel in Albania is becoming a phenomenon that might risk the stability of the healthcare system with its upgrading intensity. It also contributes to lowering the quality of services rendered and at the same time reduces the necessary transfer of knowledge to the younger generations. Quantitative research performed during 2014, outlines and frames the problems and causes for the migration in five basic categories: economic, professional, political, personal and social factors for migration, including questions concerning the index of satisfaction for the profession. In order to respond to the objective of the study, doctors were invited by email to fill online the questionnaire in Survey Monkey webpage. The aim of this paper is to understand the “push” factors which affect the mobility of Albanian healthcare personnel. The needs for higher income, living and working conditions are the main causes of the expansive trend of migration of healthcare workers from Albania in the past several years. Still, the reasons behind migration of health workforce are multifold, ranging from economic and professional, to political and personal factors. The lack of job satisfaction and possibilities for further education and career development, poor working conditions, political pressure, the exposure to verbal and physical violence, are also the factors that stimulate the migration.